2023
DOI: 10.1371/journal.pone.0276411
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to anti-retroviral therapy adherence among adolescents aged 10 to 19 years living with HIV in sub-Saharan Africa: A mixed-methods systematic review and meta-analysis

Abstract: Background Human Immunodeficiency Virus (HIV) significantly affects adolescents globally, with the sub-Saharan Africa (SSA) reporting a high burden of the disease. HIV testing, treatment, and retention to care are low among adolescents. We conducted a mixed-method systematic review to assess anti-retroviral therapy (ART) adherence; barriers and facilitators to ART adherence and ART outcomes among adolescents living with HIV and on ART in sub-Saharan Africa. Methods We conducted searches in four scientific da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 118 publications
0
1
0
Order By: Relevance
“…Economic barriers are often interrelated with other biopsychosocial barriers and pose a barrier to optimal adherence among adolescents with HIV (Hlophe et al 2023 ; Kansiime et al 2021 ). A systematic review of studies in South Africa found that food insecurity is common in most low-socioeconomic settings in South Africa and poses a barrier to adolescents taking their ART medication as prescribed (Muchena & Kalenga 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Economic barriers are often interrelated with other biopsychosocial barriers and pose a barrier to optimal adherence among adolescents with HIV (Hlophe et al 2023 ; Kansiime et al 2021 ). A systematic review of studies in South Africa found that food insecurity is common in most low-socioeconomic settings in South Africa and poses a barrier to adolescents taking their ART medication as prescribed (Muchena & Kalenga 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same level of improvement in mortality and morbidity has not been observed amongst adolescents living with perinatal HIV infection (APHIV) [2]. There is evidence that, compared to adults and children, adolescents fail to cope with living with HIV, which is evidenced by a variety of factors such as a high rate of virological failure and loss at follow-up, as well as high defaulter rates [2][3][4][5]. United Nations Children's Fund's (UNICEF) data indicated an increase of about 50% in AIDS-related deaths among APHIV, while they observed mortality decrease among all other age groups [6].…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, the majority of APHIV are currently on a one-pill, once-daily, fixed-dose combination antiretroviral regimen (Tenofovir, Emitricibine, and Efavirenz). In South Africa, this regimen was first approved in 2013 [4,7,10]. Adherence to ART remains low among APHIV in SSA despite multiple interventions implemented to improve ART adherence [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations